LIKA-LIKU DALAM MEMBANGUN KEPERCAYAAN MUZAKKI TERHADAP LEMBAGA AMIL ZAKAT - Luthfianto, Arif; Aisya Inshira, Ataya; Satria Maulana, Bagus; Septian Karunia Putri, Candra; Setyo Dewi, Nimas; Safitri, Noviana; Syahrul Mubarok, Ridho (Wahana Islamika: Jurnal Studi Keislaman, 2024)
This article aims to examine and explore what zakat is. Zakat itself is the third Islamic obligation; not paying it out will be considered stingy, and refusing it can be categorized as infidelity. Zakat is the third pillar of Islam and is, of course, mandatory. Those who pay zakat are considered generous people, and even those who reject the requirement to pay zakat can be classified as disbelievers. The obligation to pay zakat is mentioned in the verses of the Quran, including Surah Al-Baqarah verse 43. There are 8 categories of people entitled to receive zakat, including the Poor, Needy, Amil Zakat, Converts, Slaves, Debtors, Fighters Fi Sabilillah, and Wayfarers. Before carrying out zakat activities, a Muslim, whether man or woman, must fulfill several mandatory requirements. Zakat itself is divided into 2 types, namely zakat fitrah and zakat on assets. Normative methods are used in this study. The results of this study show that cases of misappropriation in zakat management highlight the importance of accountability and transparency in zakat administration. Accountability and transparency are essential for maintaining public trust and ensuring that zakat funds truly reach those who are entitled to receive them.